Analysis of Factors Associated with Perceived Health Status Among Nursing Lecturers - Muhammad Irwan (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
BackgroundPerceived health status is an important subjective indicator reflecting individuals’ physical and psychological conditions and is closely associated with productivity in occupational settings. This study aimed to analyze factors associated with perceived health status among lecturers at the Faculty of Nursing, Universitas Padjadjaran. MethodsThis analytic observational study used a cross-sectional design. A total of 68 lecturers were included using total sampling. Data were collected using structured questionnaires assessing perceived health status and associated factors (behavioral, health service, environmental, and genetic). Data were analyzed using Chi-square tests and logistic regression, with a significance level of p < 0.05. ResultsAmong 68 respondents, 86.8% reported a positive perceived health status. Behavioral factors (p=0.001) and genetic factors (p<0.001) were significantly associated with perceived health status, while health service and environmental factors were not (p>0.05). Multivariate analysis showed that behavioral factors (p=0.012) and genetic factors (p=0.008) remained significant predictors, with behavioral factors identified as the most dominant. ConclusionBehavioral and genetic factors significantly influence perceived health status among lecturers. Workplace health promotion programs focusing on healthy behaviors and early detection of genetic risks are recommended to improve well-being and productivity.